Etiopathogenetic Similarities of Combined Forms of Localized Scleroderma and Vitiligo - Nikolay N. Murashkin; Alena A. Savelova; Roman A. Ivanov; Eduard T. Ambarchian; Alexander I. Materikin; Roman V. Epishev; Leonid A. Opryatin ("Paediatrician" Publishers LLC, 2020)
Vitiligo is a common skin disease characterized by idiopathic progressive skin hypomelanosis. Vitiligo is associated with several comorbid autoimmune diseases such as localized scleroderma. This article demonstrates the general development mechanism of these pathologies, as well as the key aspect of cross-effect between autoimmune diseases on the molecular level. Recently, dermatologists have noted the increasing number of patients suffering from combined pathologies. Such patients (in pediatrics) have torpid course of disease and no pathognomonic symptoms. That exaggerates the diagnostics and adequate therapy prescription. This leads to increased awareness among physicians of different specialties on possible combinations, clinical presentation and pathogenesis aspects of such conditions.